Book Reviews - Ken Stevens; Alan Dodds; Graham Wagner (Flexible Learning Association of New Zealand, 2012)
Reviews of: Race, P.& McDowell, S.(1996) 500 computing tips for teachers and lecturers. Kogan Page, London. Evans, T. & Nation, D. (eds) (1996) Opening Education - policies and practices from open and distance education. Routledge, London and New York. Raggatt, P., Edwards, R., & Small, N. (eds.) (1996) The Learning Society: Challenges and Trends. Routledge, London and New York. Lockwood, F. (ed.) (1995) Open and Distance Learning Today. Routledge Studies in Distance Education, London.